Human Subjects Research Regulation - I.Glenn Cohen, Holly Fernandez Lynch (The MIT Press, 2014)
Tens of billions of dollars are spent each year on clinical research of investigational treatments in the United States and around the world ( Getz 2010 ), but clinical trials represent only the tip of the iceberg when it comes to human subjects research. From the scientists involved in multimillion dollar clinical trials of potential HIV vaccines, to the university anthropologist who wants to conduct interviews in Chile of shamans in the Mapuche tribe (or nation as they prefer to be called) to understand the ways in which they attach mystical significance to legal texts, to the psychology graduate student studying how other students allocate funding in a simulated charity, all of these disparate researchers have to wrestle with largely the same framework for regulating human subjects research. The history and details of this framework — which entails elements of both paternalism and preservation of individual autonomy — are described in greater depth in the next chapter and many of the subsequent ones. In the United States it emerged out of the horrors of the Nazi experiments, confronted by the world in the Doctors ’ Trials at Nuremberg following World War II, as well as the now-infamous Tuskegee syphilis study conducted by government researchers on poor black men in Alabama from 1932 to 1972. The framework has gone through a number of iterations since the initial regulations for protecting human subjects in research supported or conducted by the Department of Health, Education, and Welfare (the precursor to today ’ s Department of Health and Human Services) were first promulgated in 1974 (Porter and Koski 2008), but its foundational essence has remained largely intact since then. As the authors in this volume catalog, however, the US regulatory system governing human subjects research has a number of major deficiencies: it is slow, it is expensive, it is inconsistent in part due to its decentralized review system, it fetishizes the formalities of informed consent,and it overprotects patients from small potential risks while failing to compensate them for more serious injuries sustained during research, among many other problems. In general, it seems poorly equipped to deal with the realities of human subjects research in the twenty-first century.